On the regularity of null cones and geodesic spheres - Gutiérrez-López, Manuel; Olea-Andrades, Benjamín (Springer, 2023)
We show a property on the null cones in a Lorentzian manifold near a conjugate point, which contributes to the understanding of the behaviour of the exponential map. We also give an analogous property in the Riemannian case.
Keywords: Hipersuperficies; Geometría semi-riemanniana; Null hypersurface; Rigging technique; Null cone; Null conjugate point